The Private Sector and Criminal Justice (Palgrave Macmillan UK, 2018)
This book brings together a collection of essays by leading criminologists to explore the relationship between the private sector and criminal justice. The private sector has become an increasingly important 'partner' in contemporary criminal justice with the unprecedented growth of public sector 'outsourcing' arrangements. This has resulted in an increasingly pluralised and marketised landscape of contemporary criminal justice. This edited collection examines these developments in different jurisdictions as well as in a wide range of criminal justice contexts and sectors including: the private security sector, policing, prisons, probation and community sanctions, and electronic monitoring. In so doing, it addresses fundamental normative, ideological and ethical debates about the role of the private sector within this new and evolving landscape, as well as descriptive and analytical questions about how criminal justice structures, agencies and processes functio n and with what effect. The Private Sector and Criminal Justice is essential reading for scholars and students of criminology, penology, policing, security, criminal justice and organisational and management studies. It is also an invaluable resource for criminal justice practitioners.